Personality Branding sebagai Peluang Karir Generasi Alpha: Personality Branding as a Career Opportunity for Generation Alpha - Sari, Novi Primita (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This community service program aims to improve personality branding literacy in the Alpha generation as a strategy to build career opportunities in the digital era. This activity targets students of SMK Idhotun Nasyikin with an edutainment approach, communication training, and aptitude tests. As a digital-native, Generation Alpha has excellent potential to build an authentic self-image through social media and other digital platforms. The mentoring results showed a significant increase in understanding the basic concepts of personal branding, such as self-identity, digital reputation management, and visual content strategies through Instagram. The score evaluation showed that participants had been able to create digital profiles that reflected the uniqueness and consistency of their brands, although the aesthetic and engagement aspects still needed strengthening. This finding confirms that personality branding literacy is a strategic competency that needs to be instilled early on as a provision for entering the world of work and digital entrepreneurship. It is recommended that this material be integrated into the vocational curriculum to strengthen the competitiveness of the younger generation.